(untitled) (Bangladesh Medical Journal, 2012)
The aim of the study was to investigate sexual lifestyle and socioeconomic profile of the brothel based sex workers. The studied population was sex sellers of Dauladia brothel, Rajbari, the largest brothel in Bangladesh. A total of 113 sex sellers were recruited consecutively following the defined selection criteria. The study period was from July 2009 to January 2010. The research instrument was an interviewer questionnaire. Results showed that most of the (92.0%) of the sex workers were illiterate. Their monthly income was Taka 6 thousands to 25 thousands. Majority of them were adolescent or young adult and unmarried. About 51.3% of them had no children and rest had children. The factors induced to adopt sex selling profession were broker’s motivation and/or misguide, poverty or financial insolvency, willingly and born in the brothel. Three to fifteen clients visited the sex sellers every day. Nearly 72.0% of them used condom by their clients, 23.9% oral pills and condom, and were 4.4% injections and condom respectively. Knowledge of the sex sellers about STIs including HIV/AIDS was found satisfactory. An alarming finding was that majority of them had poor knowledge about STIs & HIV/AIDS. About 29.2% fathers of them were farmers, 21.3% day labours, 19.4% small businessmen, 10.0% transport driver and 4.4% service holders. Client’s occupation was 38.1% business men, 30.9% transport workers, 19.4% service holders, and 11.6% were students. Altering their sexual act and behaviors and substitute rehabilitation may be the applicable way to overcome this social problem. DOI: http://dx.doi.org/10.3329/bmj.v39i3.9946 2010; 39(3) BMJ